Beyond the speech community: On belonging to a multilingual, diasporic, and digital social network. (September 2019) - Jacquemet, Marco
Abstract: The experience of linguistic globalization, and the sociolinguistic disorder it entails, requires a serious retooling of most basic units of sociolinguistic analysis—foremost among them the speech community. The randomness and indeterminacy of contemporary flows of people, knowledge, texts, and commodities across social and geographical space is affecting the linguistic ideological boundaries of inclusion and exclusion. In particular, we can no longer assume that shared knowledge, especially indexical knowledge, can still provide a common ground to bind people together, negotiate conflicts, and share/transmit ideologies. Using data from a digital ethnography of a multilingual, diasporic social network, this paper will discuss the development of social formations in contemporary transidiomatic environment. The claim of this paper is that is now time to go beyond the study of speech communities, even if based upon a "linguistics of contact", to examine social formations composed by both humans and digital agents and shaped by a linguistics of xenoglossic becoming, transidiomatic mixing, and digital recombinations. Highlights: The concept of speech community needs to be retooled. Cultural globalization is affecting the linguistic ideological boundaries of inclusion and exclusion. We can no longer assume that shared knowledge, especially indexical knowledge, can still provide a common ground to bind people together, negotiate conflicts, and share/transmit ideologies. It is now time to go beyond the study of speech communities, to examine social formations composed by both humans and digital agents and shaped by a linguistics of xenoglossic becoming, transidiomatic mixing, and digital recombinations.